Positive Law and Sharia Review of Waqf Deposit Products with a Content Analysis Approach - Asnan Purba; Yaser Taufik Syamlan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Waqf Deposits are a form of investment where funds are set aside for waqf purposes and are managed by Sharia Financial Institutions. The profits can be used for social or educational activities. This research uses a qualitative method of literature study/library search which tries to compare several existing regulations, then tries to conclude whether there is a need for new regulatory provisions related to waqf deposits, especially integration between waqf deposit management and the latest regulations, Indonesia Financial Services Authority (OJK) involvement in supervising waqf deposits, protection Customer Law in Waqf Deposit Products. This research provides an in-depth study of aspects of legal protection for customers who own funds in waqf deposit products, considering that there is still limited literature that examines this topic comprehensively. This research not only refers to existing laws, but also integrates the latest regulatory developments related to sharia fintech and the management of waqf funds in the form of deposits. This research also makes a significant contribution in understanding and developing waqf deposit products that comply with sharia law and regulations applicable in Indonesia.